Effect of bromide ions on formaldehyde formation during ozonation of drinking waters - (:unkn) unknown (IWA Publishing, 2001)
The effect of bromide ions on formaldehyde formation during ozonation was studied by ozonating solutions of Suwannee River humic acids at three different bromide ion concentrations in a semi-batch system. No significant effect was observed during the initial 20 minutes of ozonation in the presence of 1 mg/l of bromide and during 10 minutes of ozonation in the presence of 10 mg/l bromide ions in solution. However, upon further ozonation, formaldehyde formation was significantly slower in the humic acid solution containing 10 mg/l of bromide. The effect of bromide ions at the later stages of ozonation was due to the formation of oxidized bromide species, which act as efficient hydroxyl radical scavengers in the system. The presence of 10 mg/l chloride ions in solution did not affect formaldehyde formation during 50 minutes of ozonation.
Keywords: Bromide; Disinfection by-products; Formaldehyde; Ozonation